Investigating EFL Instructors’ Use of Oral Corrective Feedback Types in the Classrooms (Raparin Journal of Humanities (RJH), 2024)
This study investigates EFL university instructors’ understanding and conceptualization of oral corrective feedback (OCF) vis-à-vis their teaching peculiarities. Participants in the current study involve 140 EFL instructors from various colleges and faculties with various specialities in universities in Kurdistan Region, Iraq. Among them, 87 participants were males and 53 participants were females, and they aged between 23 and 60. The instrument used in this study for data collection includes questionnaires, which have been adopted from previous research (e.g., Fukuda, 2004; Park, 2010; Yüksel et al., 2021). The results show that most of the participants tend to yield OCF moderately, and a considerable number of the instructors would correct students’ oral errors quite often. Moreover, the instructors tend to orient to global errors more than local errors. The instructors also would practice delayed OCF more often than immediate OCF. Furthermore, the most frequently deployed strategies involve clarification requests and recast for grammatical errors and recast and metalinguistic feedback for both phonological and lexical errors. Finally, the main source of providing feedback is the teacher.